Determinants of wadiah bonus in sharia banks: Evidence from Indonesia - Sitorus, Eva Afrilisa; Santri Yanti, Nur; Inayah, Nurul (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Research on wadiah bonuses within the context of Sharia banks remains an engaging issue in Islamic countries. This research aims to examine the impact of wadiah savings deposits, profit-sharing income, murabahah income, and Ijarah rental income on the distribution of wadiah bonuses to customers in Sharia banks. Employing a quantitative approach, this study utilizes secondary data from the monthly financial reports of PT Bank Syariah Indonesia covering the period from 2020 to 2023. The analysis is conducted using multiple linear regression. The findings reveal that wadiah savings funds do not significantly affect wadiah bonuses, indicating that changes in wadiah savings amounts do not impact the distribution of these bonuses. Profit-sharing income, however, has a significant effect on wadiah bonuses, suggesting that fluctuations in Wadiah bonuses are influenced by profit-sharing income. In contrast, Murabahah income does not significantly affect wadiah bonuses, indicating that changes in Murabahah income do not impact the distribution of these bonuses. On the other hand, Ijarah income has a significant effect on wadiah bonuses, demonstrating that variations in Ijarah income influence the distribution of wadiah bonuses.